Evaluation of cervical cancer awareness and preventive practices among nurses at Princess Christian Maternity Hospital, Sierra Leone - Suma, Abdul Aziz; Archer-Campbell, Doreen Folakemi; Jabba, Kai; Kamara, William; Sampha, Amara; Bah, Ishmael; Turay, Abdulai (International Journal Of Community Medicine And Public Health, 2026)
Background: Cervical cancer remains a leading cause of preventable morbidity and mortality in sub-Saharan Africa, where organized screening and human papillomavirus (HPV) vaccination coverage are limited. Nurses are pivotal for counselling, triage, and referral within reproductive health services, yet their knowledge and personal engagement with screening strongly influence patient uptake. Empirical data from Sierra Leone especially from tertiary referral settings are scarce, hindering tailored capacity-building and service navigation interventions. Objectives were to assess nurses’ knowledge, awareness, and practices regarding cervical cancer, HPV, screening, and vaccination at a national referral hospital. Methods: Cross-sectional survey at Princess Christian Maternity Hospital (PCMH), Freetown (25 November 2023 to 30 January 2024). Stratified sampling by cadre; n=117 (response rate 90% of the 130 minimum). Structured self-administered questionnaire with prespecified adequacy thresholds (causes ≥3/4; risk factors ≥5/8; symptoms ≥3/5; transmission ≥4/6; preventive practices ≥3/5). Descriptive statistics and χ²/Fisher’s exact tests (p<0.05). Results: Only 35.9% identified HPV as the cause; adequacy was 48.7% for causes, 21.9% for symptoms, and 26.6% for risk factors. Knowledge differed by cadre (causes p=0.001; symptoms p=0.011), highest among BSc nurses and midwives, lowest among SECHN; no associations with age or experience. Awareness of screening was 47.9%; among the aware, correct timing “before sexual debut” was 14.3% and correct interval “every 3-5 years” 21.4%. Screening uptake in the past five years was 29.1%. Leading barriers were not knowing where to test (55.4%), perceived no need (20.5%), fear of procedure (14.5%), and fear of results (9.6%). Motivators were free services (44.1%) and provider advice (26.5%). Vaccine awareness was 32.5%; 97.4% of those aware would recommend it. Conclusions: Nurses at PCMH, Freetown, showed suboptimal HPV-specific knowledge and low recent screening (29.1%), with significant cadre differences and navigation barriers. Targeted, cadre-specific training, clear service navigation aids, and provider-initiated, free/low-cost screening offers could rapidly improve nurses’ knowledge, uptake, and patient counselling.